The Use of Anglicisms in Various Thematic Fields: An Analysis Based on the Corpus de Referencia del Español Actual - Eugenia Esperanza Núñez Nogueroles (Anglica. An International Journal of English Studies)
This piece of research presents an analysis of the use of anglicisms in the Spanish press at the beginning of the 21st century. Specifically, it concentrates on their distribution in texts belonging to different thematic domains. Thus, the purpose of this study is to establish a ranking of specialised fields in terms of the frequency with which anglicisms are employed in them. In order to do so, the Corpus de Referencia del Español Actual (CREA), compiled by the Real Academia Española, is used as the source for texts, which supports the reliability and representativeness of the present work.